Mutations in the gene of human type IIb sodium-phosphate cotransporter SLC34A2 - Lituiev, D.S.; Kiyamova, R.G. (Вiopolymers and Cell, 2010)
Type IIb sodium-phosphate cotransporter (NaPi2b) provides phosphate intake in the cells of some epithelial tissues, osteoblasts and odontoblasts. Abnormal expression of NaPi2b has been detected in some types of epithelial tumors. An alteration in NaPi2b activity, caused by mutations in transporter gene SLC34A2, has been recently revealed in patients with pulmonary alveolar microlithiasis, an autosomal recessively inherited disease, characterized by deposition of calcium-phosphate precipitates in the lungs. In the present study we have combined the information about all mutations found to date in the coding sequence of SLC34A2 and its transcript, compiled their map, and analysed their relevance to the function of NaPi2b.